COMPOUND RUNS OF LOGS CALCULATION: ACCOUNTING OF LONGITUDINAL FORCES’ AND BENDING MOMENTS’ INTERACTION - V. A. Utkin; P. N. Kobzev; E. G. Shatunova (Вестник СибАДИ)
Introduction. Studying the designing and constructing experience of beam bridges with composite log girders indicates the possibility of the load bearing capacity rising of the structures and their further usage in the IV and V categories bridges’ construction under A-11 and H-11 loads. The purpose of the research is to evaluate the effect on the magnitude and distribution of shear forces in shear bonds, considering the permissible pliability of fixation in wood and on the nature of the stress state change in the rods of the composite girders.Materials and methods. The authors presented the construction of the composite girder in the form of three rows united by means of tie bolts and gaskets of four-tier single-row composite girders and made of edged logs. The proposed studying method of a composite girder stress-strain state with discrete placement of concentrated shear bonds in the joints based on the classical method of forces for rod systems, taking into account the interaction of longitudinal forces and bending moments arising in the rods composing the girder of unknown forces in the shear bonds.Results. The determination of single displacements with joint account of bending and stretching-compression deformations haв a significant impact on the redistribution of shear forces in the direction of increasing them in the support zones and reducing them in the middle of the span, and, consequently, on the design of the connecting elements. The character of distribution of normal stresses on the stretching-compression indicated the rods’ girders between relationships under the eccentric compression (stretching).Discussion and conclusions. The proposed solutions demonstrate the most accurate assessment of the composite girders in the structures of spans wooden bridges and present the application possibility in modern conditions.Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.